The near disappearance of genital warts in young women 4 years after commencing a national human papillomavirus (HPV) vaccination programme. Issue 7 (4th October 2011) - Read, Tim R H; Hocking, Jane S; Chen, Marcus Y; Donovan, Basil; Bradshaw, Catriona S; Fairley, Christopher K
Abstract : Background: Australia provided free quadrivalent human papillomavirus vaccines to 12–18-year-old girls and women aged ≤26 years from mid-2007 until the end of 2009. After this time, only girls aged 12–13 years had access to free vaccines. Methods: Before and after the study, of the proportion of new patients attending Melbourne Sexual Health Centre from mid-2004 to mid-2011, diagnosed with genital warts (GW) by risk group. Results: From July 2004 to June 2011, 52 454 new patients were seen at Melbourne Sexual Health Centre and 5021 (9.6%, 95% CI 9.3% to 9.8%) were diagnosed with GW. From July 2004 to June 2007, the proportions with GW either increased or did not change in all groups. Comparing the two 12-month periods of 2007/2008 and 2010/2011, GW declined in women under 21 years from 18.6% to 1.9% and in heterosexual men under 21 years from 22.9% to 2.9%. The ORs per year for diagnosis of GW adjusted for number of sexual partners from July 2007 until June 2011 in women and heterosexual men <21 years were 0.44 (95% CI 0.32 to 0.58) and 0.42 (95% CI 0.31 to 0.60), respectively. There was no significant change in GW in women ≥30 years (OR 0.97, 95% CI 0.84 to 1.12), heterosexual men ≥30 years (OR 0.97, 95% CI 0.89 to 1.06) or in homosexual men (OR 0.95, 95% CI 0.85 to 1.07). Conclusion: The dramatic decline and near disappearance of GW in women and men under 21 years of age, 4 years after commencing this programme, suggest that the basic reproductive rate has fallen below one.